(2x+3)/(x+2)=3/2Math problem; solve the following rational equation

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You need to have all terms to the left side.

Subtracting 3/2 both sides yields:

`(2x+3)/(x+2) - 3/2 = 0`

You need to bring both fractions to a common denominator such that:

`(2(2x+3) - 3(x+2))/(2(x+2)) = 0`

Opening the brackets yields:

`(4x + 6 - 3x - 6)/(2(x+2)) = 0`

...

Unlock
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial

You need to have all terms to the left side.

Subtracting 3/2 both sides yields:

`(2x+3)/(x+2) - 3/2 = 0`

You need to bring both fractions to a common denominator such that:

`(2(2x+3) - 3(x+2))/(2(x+2)) = 0`

Opening the brackets yields:

`(4x + 6 - 3x - 6)/(2(x+2)) = 0`

`` `x/(2(x+2)) = 0`

The denominator of the fraction must not be zero => `x+2 != 0`  => `x != -2` .

If the fraction yields 0 => x = 0.

The solution to the given equation is x = 0.

Approved by eNotes Editorial Team